Optimax / Faridah Jusoh ... [et al.] - Jusoh, Faridah; Ahmad, Nor Antasya; Mohamad Azmi, Nor Azilawati; Taibon, Zanariah (Faculty of Information Management, 2003)
Optimax is a partnership company. Four members share this business. We will start our business by 2004. Optimax is located at lot 1-15, 1st floor, Alam Sentral Plaza, Jalan Majlis, Seksyen 14,40000 Shah Alam, Selangor Darul Ehsan.